Contradiction between technocratic and humanistic systems of values - Kazakevich, M. I.; Guzova, I. I. (Science and Transport Progress, 2013)
Purpose. The purpose of the paper is determination of difference between technocratic and humanistic value systems. The authors also suggest to outline the range of issues specific to modern technological civilization, reflect its controdictory nature, as well as to focus on the university activity fields concerning formation and/or restoration of technocratic and humanitarian balance. Methodology. The most important methodological principle of the work is a systematic approach. It has determined logic of description and conclusion. During the study authors analyzed separate aspects of social development of the late 20th – early 21st centuries, as well as content analysis of the global information flow (documentary and non-documentary) on this topic and their own observations, obtained during the implementation of long-term educational and scientific practices at the university. It is, for example, drawing up a comparative table of technocratic and humanistic value systems. The authors have conducted a comparative analysis of 2 Sociological Research data (2009 and 2013 years) among university youth of Dnipropetrovsk "Modern Library by Students′ Eyes" and trending concerning the issues about the role of reading in the students lives. Findings. The difference between the technocratic and humanistic value systems was determined. Contemporary problems of the personal intellectual development in the process of education and training in technical universities during the dominance of technocratic value systems were outlined. Attention is focused on the university directions on formation and / or restoration of technocratic and humanitarian balance. Originality. The authors have analyzed and outlined a range of issues specific to contemporary industrial civilization, its controversial nature was reflected. Rebalancing of the technocratic and humanitarian is one of the major tasks in our time. The directions of universities activities were determined. Practical value. Highlighting the several problems solving necessity will ensure harmony in the interaction of technocratic and humanistic value systems. The material presented in this article can be used in the teaching of Humanities and Social Sciences, in the activities of various cultural and informational, mass-cultural, social structures of the University; the activity directions of which suggest a sociocultural understanding of technology, its achievements, the consequences of its development, the responsibility for its use, contributing to the restoration of harmony in the development of human and technological spheres.